Design and Control of an Underwater Launch System - Christian Corwel; George Zoghbi; Stevan Webb; Abhishek Dutta (IEEE Access, 2020)
The ability to launch, or otherwise deploy, a cylindrical body such as an unmanned vehicle, from an outer tube in an underwater environment continues to be of interest to the marine community. Applications of such technologies include the use of small unmanned underwater vehicles (UUV's) deployed from deep ocean craft to support oil exploration efforts or inspection of damaged infrastructure. Historically, these payloads are deployed from their containment tube through the use of a water slug generated from a pump which pushes the vehicle into the open ocean environment.The objectives of this project are to identify and demonstrate a method to launch a cylindrical body from the launch tube utilizing an electromagnetic scheme. It was found that the solenoid coil launching mechanism was the most effective for an underwater launcher. A design was created, modeled in simulations, and finally built and tested to prove its validity. It was found that the solenoid coil launcher could effectively expel a payload with ample exit velocity, low noise, and could be reloaded several times within a minute.